(untitled) (Fiep Bulletin - online, 2014)
School backpacks have been used by more and more students, specially children. Their use, however, can lead to posture disorders in the future, as the World Health Organization remarked. The WHO warned the public that 85% of general population had, have or will have back pain due to posture disorders beginning in childhood because the development of bones is incomplete in this period. For this reason, many Brazilian States tried to reduce the risk for developing posture-related disorders and passed a law to restrict the weight of school backpacks. According to law, children of school age must carry school backpacks weighing less 10% of their body weight. To verify whether the weight of the school backpacks used by the study subjects complies with that which should be recommended. In addition, to verify the possibility of associated disease causation. The epidemiological cross-sectional quantitative and descriptive study was carried out in a convenience sample of forty students (n = 40) attending the first, second, third, and fourth grades who used school backpacks daily. A questionnaire was applied in the presence of parents and school board of directors for direct data collection. Its questions were used as study variables. Study results are presented as percentages and absolute numbers in simple frequency graphs and tables. The present study complied with legal and ethical requirements. The present study found that 60.00% of students carried a backpack with each strand on each shoulder; 60.00% carried a backpack weighing more than 10% of their body weight. As for pain, 61.35% of students reported cervical and thoracic pain while 52.83% and 50.78% reported leg and right shoulder pain, respectively. This finding suggests that pain can be related to exceeding load. The results of the present study suggest that the sites of pain can be related to the exceeding weight of school backpacks.